1983
DOI: 10.1007/bf02671339
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids in rapeseed and mustard

Abstract: The compositions of free phenolic acids in rapeseed flours of diverse origin and white mustard were highly variable but represented less than 10% of the total phenolic acids. Phenolic acids released from hydrolysis of soluble esters constituted the major fraction, with Polish varieties having higher levels than a Canadian variety or white mustard. Yellow Sarson contained low levels of phenolic acids. Sinapic acid isomers constituted over 94% of the 13 phenolic acids found in the rapeseed varieties. Only traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 12 publications
10
53
1
Order By: Relevance
“…Phenolic acids present in the crude extract were fractionated into free and bound forms according to the procedure described by Koz / lowska et al (10) and Zadernowski (11). A 0.5-g sample of dried crude phenolic extract was suspended in 50 mL of triply distilled water, acidified to pH = 2 using 6 N HCl, and extracted five times with diethyl ether (1:1, vol/vol) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic acids present in the crude extract were fractionated into free and bound forms according to the procedure described by Koz / lowska et al (10) and Zadernowski (11). A 0.5-g sample of dried crude phenolic extract was suspended in 50 mL of triply distilled water, acidified to pH = 2 using 6 N HCl, and extracted five times with diethyl ether (1:1, vol/vol) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Kozlowska et al (1983) have shown that the total content of insoluble-bound phenolics in rapeseed flours, in mg per 100 g meal, ranged from 3.2 in Yellow Sarson to 5.0 in Gorczanski, a Polish rapeseed variety. They also identified nine phenolic acids in this fraction.…”
Section: Insoluble-bound Phenolic Acidsmentioning
confidence: 99%
“…Minor phenolic acids were p-hydroxybenzoic, vanillic, gentisic, protocatechuic, syringic, pcoumaric, ferulic, and caffeic acids. In addition, chlorogenic acid was found in trace amounts (Lo and Hill 1972;Kozlowska et al 1975Kozlowska et al , 1983Krygier et al 1982).…”
Section: Ph Enolic Aci Ds General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20, 671, dehulled [7 1, 721, myrosinase-icactive and myrosinase-active seeds [I%, 1721; the mode of solvent employment: 0.01 N NaOH solution [71, 72, 1581 or 0.01 N ethanolic NaOH solution [67], water and sodium chloride solution [172].…”
Section: Oil Exfracfion I T Tmentioning
confidence: 99%